Structural and Biological Studies on Some Coper(II) Macrocyclic Complexes - Ambwani, Jitendra; Bansal, N.L.; Kaushik, Kshama (Asian Journal of Chemistry, 2010)
Two new macrocyclic complexes were synthesized having the formulae Cu[DPAODAH](BF4)2 and Cu[DPATDPH](BF4)2 {where [DPAODAH] = diphenyl diacetic acid-N-oxy diacetic acid dihydrazone and [DPATDPH] = diphenyl diacetic acid-N-thiodipropionic acid dihydrazone and BF42 = Tetrafluoroborate. The complexes were characterized using molar conductance, magnetic studies and infrared and electronic spectral data and have been assigned octahedral geometries. The complexes were screened for their biological studies against bacteria S. aureus and E. coli and fungi A.flavus and C. albicans. The complexes were found to have intense antimicrobial activity as contrasted with ligand fragments.